Designing model of biologic product buildings - Dabaghchi, Samaneh (2008)
The physical health of the human kind and the environment around including medium or direct elements serving to him is one of the main factors of the life of the humanity. Since many years ago the medical sciences has been developing applying new technology and sciences every day. Today, other sciences and new technologies support the sciences of the health branch in line with meeting the welfare and safe life needs of the humanity. Similarly, architecture has taken effective steps with the suitable designing of the biologic spaces in this relation.Diagnosis of infections, prevention of infections and taking care of patients each one has it own special method discovered during years by the expert and professionals of this science, who were used to do this with the help of the other science. On the other hand, for the creation of the new solution and issuance of new methods, a suitable structural space is needed in line with meeting the needs of the collection. For reaching this purpose that is the same called "Good architectural at the service of industry and medical section", the architectural engineers should apply their best in designing an applied collection having dominance on the performed activity and application of the advanced production systems in order to supply the safe working environment for the personnel with the creation of fascinating and diverse spaces which motivate the personnel giving them comfort at the same time.It was almost several years ago that W.H.Oi has compiled G.M.Pii rules in line with the health of community and quality and safety of the products and introduced it being enforceable in all the related centers. The above- mentioned standards have believed that the building and installations engineering has a great role in reaching the optimized quality.